Hydrogen conduction type hybrid silicon dioxide particle, preparation method thereof and composite membrane electrode
By grafting imidazole polymers on the surface of silica particles to form hydrogen-conducting hybrid silica particles, the problem of difficult to maintain mechanical stability when improving proton conduction performance is solved, and the efficient water electrolytic performance of composite membrane electrodes is achieved.
Patent Information
- Application Number
- CN202411852085.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-04-15
AI Technical Summary
While improving the proton conduction performance, existing proton exchange membranes are difficult to maintain mechanical stability, resulting in limited application in electrolytic water-lytic devices.
By modifying the silica particles, the imidazole polymer is treated with a silane coupling agent and grafting the imidazole polymer on its surface, forming hydrogen-conducting hybrid silica particles, which are used in a composite proton exchange membrane to regulate their interaction with the matrix interface, thereby improving proton conduction performance and mechanical stability.
The overall proton conduction performance and mechanical stability of the composite proton exchange membrane are achieved, which improves the "trade-off" effect and improves the water electrolytic performance.
Smart Images

Figure CN119824477A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the technical field of hydrogen production by water electrolysis, and in particular to a hydrogen-conducting hybrid silicon dioxide particle and a preparation method thereof, and a composite membrane electrode. Background Art
[0002] As a key component of proton exchange membrane water electrolysis (PEMWE), proton exchange membrane (PEM) mainly plays the role of conducting protons and isolating the anode and cathode, which requires it to have excellent proton conductivity and mechanical stability. However, the current research on proton exchange membranes has a trade-off effect (balance effect) in which proton conductivity and mechanical stability are difficult to balance, which limits its efficient application.
[0003] At present, the simplest and most efficient way to improve the trade-off effect is multiphase hybridization, that is, adding nanofillers to the PEM matrix to synergistically improve the performance of the composite PEM through the mechanical stability of inorganic materials. However, due to the poor interface interaction between the inorganic filler and the PEM matrix, the inorganic filler cannot be evenly dispersed in the PEM matrix, which limits its application in water electrolysis devices. Summary of the invention
[0004] In order to solve the above technical problems, the present disclosure provides a hydrogen-conducting hybrid silica particle and a preparation method thereof, and a composite membrane electrode.
[0005] The present disclosure provides a hydrogen-conducting hybrid silica particle, comprising modified silica particles and an imidazole polymer grafted on the surface of the modified silica particles, wherein the grafting amount of the imidazole polymer grafted on the surface of the modified silica particles is 5.5-13%, for example, 6%, 7%, 8%, 9%, 10%, 11%, 12%, etc.
[0006] As a preferred technical solution of the present disclosure, the mass ratio of the modified silica particles to the imidazole polymer is (85-95):(5-15), for example, 86:14, 87:13, 88:12, 89:11, 90:10, 91:9, 92:8, 93:7, 94:6, etc.
[0007] As a preferred technical solution of the present disclosure, the density of the hydrogen conducting groups on the surface of the modified silica particles is 0.05-0.2 μmol / m 2 , for example 0.08 μmol / m 2 , 0.10μmol / m 2 , 0.12 μmol / m2 , 0.15 μmol / m 2 , 0.18 μmol / m 2 wait.
[0008] The surface of the hydrogen-conducting hybrid silica particles provided by the present invention is covalently linked to an imidazole polymer, so that the density of hydrogen-conducting groups on the surface of the hydrogen-conducting hybrid silica particles is controllable. When applied to a proton exchange membrane, the interaction with the substrate interface can be regulated, thereby simultaneously regulating the overall proton conduction performance and mechanical stability of the composite proton exchange membrane.
[0009] As a preferred technical solution of the present disclosure, the modified silica particles are silane coupling agent modified silica particles.
[0010] In the present disclosure, by treating silica particles with a silane coupling agent, the obtained modified silica particles can promote the surface cavitation bubble dynamics behavior and thus promote the generation of free radicals. At the same time, the introduced imidazole polymer serves as a hydrogen bond acceptor unit. Through controllable grafting of the imidazole polymer, hydrogen-conducting hybrid silica particles with controllable hydrogen bond acceptor density can be finally obtained.
[0011] As a preferred technical solution of the present disclosure, the silane coupling agent is a silane coupling agent containing a carbon-carbon double bond, and preferably the silane coupling agent is γ-methacryloxypropyltrimethoxysilane.
[0012] The modified silica nanoparticles provided by the present disclosure can affect the concentration of sono-induced free radicals, and thus can regulate the grafting density of hydrogen bond receptors on their surfaces.
[0013] As a preferred technical solution of the present disclosure, the particle size of the silicon dioxide particles is 100-200 nm, for example, 120 nm, 150 nm, 160 nm, 170 nm, 180 nm, 190 nm, etc.
[0014] As a preferred technical solution of the present disclosure, the silicon dioxide particles are silicon dioxide particles prepared by hydrolysis.
[0015] As a preferred technical solution of the present disclosure, the polymerization monomer of the imidazole polymer is an imidazole compound with a carbon-carbon double bond, preferably vinyl imidazole and / or 1-propylene imidazole.
[0016] In a second aspect, the present disclosure provides a method for preparing the hydrogen conductive hybrid silica particles according to the first aspect, the preparation method comprising the following steps:
[0017] (1) reacting silica particles with a silane coupling agent to obtain modified silica particles;
[0018] (2) Grafting imidazole monomers onto the surface of the modified silica particles and performing an in-situ polymerization reaction to obtain the hydrogen conductive hybrid silica particles.
[0019] As a preferred technical solution of the present disclosure, the mass ratio of the silica particles to the silane coupling agent is (1-5):(1-5), preferably 1:1.
[0020] As a preferred technical solution of the present disclosure, the reaction in step (1) is carried out in an alcohol-water solution, and preferably the volume ratio of the alcohol to water is 1:1.
[0021] As a preferred technical solution of the present disclosure, the reaction temperature of step (1) is 70-75°C, such as 71°C, 72°C, 73°C, 74°C, etc., and the reaction time is 4-6h, such as 4.5h, 5h, 5.5h, etc.
[0022] As a preferred technical solution of the present disclosure, step (2) is: after mixing the modified silica particles with the imidazole monomer in a solvent (preferably DMF and a small amount of water), a graft polymerization reaction is carried out using an ultrasonic-aeration method to obtain the hydrogen-conducting hybrid silica particles.
[0023] As a preferred technical solution of the present disclosure, the mass ratio of the modified silica particles to the imidazole monomer is 1:(5-20), preferably 1:10.
[0024] As a preferred technical solution of the present invention, in the ultrasound-exposure method, the ultrasound mode is inserted ultrasound with a power of 500-750W, for example, 520W, 550W, 580W, 600W, 620W, 650W, 680W, 700W, 720W, etc., a frequency of 20-25kHz, for example, 21kHz, 22kHz, 23kHz, 24kHz, etc., an amplitude of 20-40%, for example, 24%, 25%, 28%, 30%, 32%, 35%, 38%, etc., and a temperature of 4-15°C, for example, 8°C, 10°C, 12°C, 14°C, etc.
[0025] As a preferred technical solution of the present disclosure, in the ultrasound-exposure method, the number of ultrasound-exposure cycles is 3-24 times, for example, 6 times, 8 times, 10 times, 12 times, 14 times, 15 times, 16 times, 18 times, 20 times, 22 times, etc.
[0026] The present invention discloses a modified silica which can promote the generation of free radicals by treating silica with a silane coupling agent, and then using an imidazole compound as a hydrogen bond acceptor unit, and using an aeration-assisted sonochemical method. By changing the number of ultrasound-aeration cycles, the polymerization process of the hydrogen bond acceptor monomer on the surface of the modified silica can be precisely regulated to achieve controllable grafting, thereby finally obtaining modified particles with different surface hydrogen bond acceptor densities as a stimulus-responsive functional composite material.
[0027] The hydrogen-conductive hybrid silica particles provided by the present disclosure, or the hydrogen-conductive hybrid silica particles prepared by the preparation method, can be used as an inorganic filler in a proton exchange membrane, while improving the proton conduction performance and mechanical stability of the proton exchange membrane.
[0028] In a third aspect, the present disclosure provides a composite proton exchange membrane, comprising a substrate and the hydrogen-conducting hybrid silica particles according to the first aspect doped in the substrate.
[0029] As a preferred technical solution of the present disclosure, the mass ratio of the substrate to the hydrogen conductive hybrid silica particles is 100:(4.5-10), for example, 100:5, 100:6, 100:7, 100:8, 100:9, etc.
[0030] As a preferred technical solution of the present disclosure, the matrix is a sulfonated polymer matrix, and more preferably is sulfonated polysulfone and / or sulfonated polyetheretherketone.
[0031] The present disclosure also provides a method for preparing the composite proton exchange membrane, comprising: mixing a dispersion containing the hydrogen conductive hybrid silica particles with a sulfonated polymer and ultrasonicating to obtain a casting solution, and forming a membrane with the casting solution to obtain the composite proton exchange membrane.
[0032] It is a preferred technical solution of the present disclosure, the power of the ultrasound is 500-750W, for example, 520W, 550W, 580W, 600W, 620W, 650W, 680W, 700W, 720W, etc., the frequency is 20-25kHz, for example, 21kHz, 22kHz, 23kHz, 24kHz, etc., and the amplitude is 20-40%, for example, 24%, 25%, 28%, 30%, 32%, 35%, 38%, etc.
[0033] The composite proton exchange membrane provided by the present invention has an electrical conductivity of up to 0.31 S / cm, which is 81.14% higher than that of pure sulfonated polysulfone (SPSF), and a swelling rate of up to 61.05%, which is 10.61% lower than that of pure SPSF.
[0034] The present disclosure also provides the composite proton exchange membrane, or the use of the composite proton exchange membrane obtained by the preparation method in a battery or a water electrolysis device.
[0035] The composite proton exchange membrane provided by the present invention generates multi-phase interfacial interactions through ultrasonic action, uses hydrogen-conductive hybrid silica particles as filler and sulfonated polymer as matrix, thereby achieving precise regulation of interfacial interactions in the composite proton exchange membrane.
[0036] In the present disclosure, the performance of the composite proton exchange membrane is regulated by regulating the hydrogen bond interactions formed between the matrix and the filler, and the overall proton conduction performance and mechanical stability are regulated. The "trade-off" effect is improved while a long-range dense hydrogen bond network is constructed, thereby improving its water electrolysis performance.
[0037] In a fourth aspect, the present disclosure provides a composite membrane electrode, comprising the composite proton exchange membrane of the third aspect.
[0038] In a fifth aspect, the present disclosure provides a method for preparing the composite membrane electrode described in the fourth aspect, the preparation method comprising: coating a cathode catalyst slurry and an anode catalyst slurry on both sides of a composite proton exchange membrane respectively and drying them to obtain the composite membrane electrode.
[0039] As a preferred technical solution of the present disclosure, the preparation method comprises:
[0040] Hydrogen conductive hybrid silica particles were dispersed in a DMSO solution containing gallic acid and subjected to insert ultrasonic treatment at room temperature to regulate the formation of hydrogen bonds. A certain amount of SPSF was then added to the DMSO solution and fully dissolved and stirred in a vacuum oven at 60°C. After cooling to room temperature, insert ultrasonic treatment was performed again to regulate the interaction between the particles and the SPSF chains. Finally, the two were fully mixed to obtain a casting solution.
[0041] The above casting solution was mixed evenly at 25°C, and then dispersed by inserting ultrasound in an ice water bath for 20 minutes (the ultrasound method was inserting ultrasound, the ultrasound power was 500W, the ultrasound frequency was 20kHz, the ultrasound amplitude was 30-40%, and the circulating water temperature was 4-15°C), and the membrane was prepared by a doctor blade method, and finally placed in a vacuum drying oven at 40°C until the solvent was completely volatilized to obtain a SPSF / SiO2@PVI composite membrane (composite proton exchange membrane);
[0042] Add IrO2 / Pt catalyst, solvent, SPSF and ultrapure water into a suitable beaker and mix thoroughly, stir evenly and then use a cell disruptor to ultrasonically disperse to obtain a slurry;
[0043] The ultrasonic nozzle sprays the pre-mixed anode and cathode catalyst slurry (containing a small amount of SPSF solution as a binder) directly onto both sides of the composite proton exchange membrane, and the composite membrane electrode is dried at 80°C.
[0044] As a preferred technical solution of the present disclosure, the SPSF is soaked in 0.05 g / mL sulfuric acid for one day, then washed with deionized water until neutral, and can be used after drying.
[0045] As a preferred technical solution disclosed in the present invention, the thickness of the casting liquid film is 1000±5 μm, and the thickness of the finally dried film is 100±10 μm.
[0046] As a preferred technical solution of the present disclosure, the anode catalyst loading is about 2.0 mgIr / cm 2 , the cathode catalyst loading is about 0.2 mg Pt / cm 2 .
[0047] As a preferred technical solution of the present invention, the mixing method of IrO2 / Pt catalyst, solvent, SPSF and ultrapure water is: the catalyst is added to part of the ultrapure water in sequence, and the remaining part of the ultrapure water, n-propanol (solvent) and SPSF solution are mixed.
[0048] Compared with the prior art, the technical solution provided by the embodiments of the present disclosure has the following advantages:
[0049] The hydrogen-conducting hybrid silica particles provided by the present disclosure can adjust the grafting density of hydrogen bond receptors on their surfaces by affecting the concentration of sono-induced free radicals, and further can adjust the interaction between them and the interface of the proton exchange membrane matrix, thereby achieving simultaneous regulation of the proton conduction performance and mechanical stability of the composite proton exchange membrane. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present disclosure and, together with the description, serve to explain the principles of the present disclosure.
[0051] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.
[0052] Figure 1 A transmission electron microscope photograph of the hydrogen-conducting hybrid silica particles provided in Example 2-1 of the present disclosure;
[0053] Figure 2The energy spectrum diagram of the hydrogen-conducting hybrid silica particles provided in Example 2-1 of the present disclosure;
[0054] Figure 3 Comparison diagram of scanning electron microscope photos of the cross section of the composite membrane electrode provided in the embodiment of the present disclosure before and after water splitting to produce hydrogen;
[0055] Figure 4 A comparison chart of the water electrolysis performance of the composite membrane electrode provided in the embodiments of the present disclosure.
[0056] Among them, SPSF is the membrane electrode provided in Comparative Example 2, SPSF / SiO2 is the composite membrane electrode provided in Comparative Example 1, SPSF / SiO2@PVI-3C is the composite membrane electrode provided in Example 5, SPSF / SiO2@PVI-6C is the composite membrane electrode provided in Example 6-1, SPSF / SiO2@PVI-9C is the composite membrane electrode provided in Example 6-2, SPSF / SiO2@PVI-12C is the composite membrane electrode provided in Example 6-3, and SPSF / SiO2@PVI-24C is the composite membrane electrode provided in Example 6-4. DETAILED DESCRIPTION
[0057] In order to more clearly understand the above-mentioned objectives, features and advantages of the present disclosure, the scheme of the present disclosure will be further described below. It should be noted that the embodiments of the present disclosure and the features in the embodiments can be combined with each other without conflict.
[0058] In the following description, many specific details are set forth to facilitate a full understanding of the present disclosure, but the present disclosure may also be implemented in other ways different from those described herein; it is obvious that the embodiments in the specification are only part of the embodiments of the present disclosure, rather than all of the embodiments.
[0059] Preparation Example
[0060] This preparation example provides a modified silicon dioxide particle and a preparation method thereof, as follows:
[0061] The silica particles obtained by the hydrolysis method (particle size is about 100-200 nm) are placed in a mixed solution of ethanol and water (volume ratio of 1:1) and ultrasonicated until the particles are completely and evenly dispersed. KH570 is added to the dispersion at a mass ratio of 1:1 to silica, and hydrolyzed at 75°C for 4 hours. The modified silica particles are obtained by freeze-drying.
[0062] Performance Test 1: Effect on the Sonoradical Concentration of the Solution
[0063] The modified silica particles were added to a water-alcohol mixed solution with a methylene blue concentration of 13.37 μmol / L. The mixed solution was subjected to an ultrasonic-aeration cycle treatment using an ultrasonic horn under circulating water temperature control. Samples were taken after different cycles for UV spectrometry testing to detect the effect of the modified silica on the concentration of sono-induced free radicals in the solution. The results are as follows:
[0064] In the initial stage, countless bubble nuclei are formed near the SiO2 nanoparticles because these nanoparticles are heterogeneous nucleation points. Subsequently, under the alternating positive and negative pressures, these cavitation bubbles will shrink and expand periodically, and drive the surrounding SiO2 nanoparticles to gather toward the center of the cavitation bubbles and disperse outward. This dynamic activity causes the SiO2 nanoparticles near the cavitation bubbles to shrink under the action of accelerated collisions between particles. Eventually, these cavitation bubbles collapse and release a large amount of energy, which activates the surface of the SiO2 nanoparticles and produces a large number of active free radicals that can be used for polymerization reactions. Therefore, the addition of silica has a significant effect on the concentration of sono-induced free radicals.
[0065] The density of hydrogen-conducting groups on the surface of modified silica particles was analyzed by GPC test, and the results were between 0.05-0.2 μmol / m 2 within the range.
[0066] Example 1
[0067] This embodiment provides a hydrogen conductive hybrid silica particle and a preparation method thereof, as follows:
[0068] (1) Weigh 0.2 g of modified silica particles (provided in Preparation Example 1) and 2 g of vinyl imidazole, put them into a 100 mL double-layer jacket filled with 60 mL of DMF and 5 mL of deionized water, insert the ultrasonic horn into the double-layer jacket glass reactor from the rubber cover, then insert a rubber tube connected to an aeration stone into the glass reactor from the rubber cover and connect it to a gas flow meter and a nitrogen bottle, another rubber tube is inserted into the rubber cover and the other end is placed in a beaker with water (below the liquid surface), and the double-layer jacket glass reactor and the circulating water pump are constructed into a closed water circuit as a cooling water circulation device during the entire reaction process.
[0069] (2) Before the reaction, an aeration stone was inserted below the liquid surface of the reaction liquid, and the nitrogen flow rate was 0.35 L / min. After 5 minutes of ventilation, the aeration stone was adjusted to be above the liquid surface of the reaction liquid. Subsequently, the reaction liquid was subjected to intermittent cyclic ultrasound for 3 cycles, with an ultrasound frequency of 20 kHz, an ultrasound power of 500 W, and an amplitude of 40% of the maximum value.
[0070] (3) After the reaction is completed, the mixture is washed with DMF and deionized water for two times, the reaction dispersion is centrifuged, and the supernatant is collected. The centrifuged product is then freeze-dried to obtain a white powder sample, which is sealed and stored at room temperature.
[0071] Example 2 (Example 2-1 to Example 2-4)
[0072] This embodiment provides a hydrogen conductive hybrid silicon dioxide particle and a preparation method thereof
[0073] The difference from Example 1 is that in this example, the number of cycles of ultrasound-aeration is different, and the specific steps are as follows:
[0074] (1) Weigh 0.2 g of modified silica particles (provided in Preparation Example 1) and 2 g of vinyl imidazole, put them into a 100 mL double-layer jacket filled with 60 mL of DMF and 5 mL of deionized water, insert the ultrasonic horn into the double-layer jacket glass reactor from the rubber cover, then insert a rubber tube connected to an aeration stone into the glass reactor from the rubber cover and connect it to a gas flow meter and a nitrogen bottle, another rubber tube is inserted into the rubber cover and the other end is placed in a beaker with water (below the liquid surface), and the double-layer jacket glass reactor and the circulating water pump are constructed into a closed water circuit as a cooling water circulation device during the entire reaction process.
[0075] (2) Before the reaction, an aeration stone was inserted below the liquid surface of the reaction liquid, and the nitrogen flow rate was 0.35 L / min. After 5 minutes of aeration, the aeration stone was adjusted to be above the liquid surface of the reaction liquid. Then, the reaction liquid was subjected to intermittent cyclic ultrasound by means of 3 minutes of ultrasound (no aeration)-1 minute of ultrasound stop (nitrogen flow in the reaction liquid) for irradiation cycle. The ultrasound frequency was 20 kHz, the ultrasound power was 500 W, and the amplitude was 40% of the maximum value, wherein:
[0076] The irradiation cycle was 6 times for Example 2-1, 9 times for Example 2-2, 12 times for Example 2-3, and 24 times for Example 2-4.
[0077] (3) After the reaction is completed, the mixture is washed with DMF and deionized water for two times, the reaction dispersion is centrifuged, and the supernatant is collected. The centrifuged product is then freeze-dried to obtain a white powder sample, which is sealed and stored at room temperature.
[0078] Example 3
[0079] This embodiment provides a composite proton exchange membrane and a preparation method thereof, as follows:
[0080] (1) 0.4 g of SPSF was added to a 20 mL glass bottle containing 1.5 mL of DMSO solution, dissolved in a 60° C. oven for 4 h and stirred for 1 h; 0.02 g of hydrogen conductive hybrid silica particles (provided in Example 1) was added thereto, and inserted ultrasonic treatment was performed for 30 min to obtain a mixed solution.
[0081] (2) The mixed solution was stirred at room temperature for 1 h, and an inserted ultrasonic rod was inserted below the liquid surface of the mixed solution and ultrasonicated for 20 min in an ice water bath at an ultrasonic frequency of 20 kHz, an ultrasonic power of 500 W, and an amplitude of 20%.
[0082] (3) The ultrasonic dispersion was scraped onto a glass plate through a 1000 μm four-sided preparation device and placed in a vacuum oven at 40° C. overnight to obtain a composite proton exchange membrane of 100-110 μm.
[0083] Example 4 (Example 4-1 to Example 4-4)
[0084] This embodiment provides a composite proton exchange membrane and a method for preparing the same.
[0085] The difference from Example 3 is that in this example, the hydrogen conductive hybrid silica particles used are those provided in Example 2, and the specific preparation method is as follows:
[0086] (1) 0.4 g of SPSF was added to a 20 mL glass bottle containing 1.5 mL of DMSO solution, dissolved in a 60° C. oven for 4 h and stirred for 1 h; 0.02 g of hydrogen conductive hybrid silica particles (provided in Example 2) was added thereto, and the mixture was treated by insert ultrasonication for 30 min to obtain a mixed solution.
[0087] (2) The mixed solution was stirred at room temperature for 1 h, and an inserted ultrasonic rod was inserted below the liquid surface of the mixed solution and ultrasonicated for 20 min in an ice water bath at an ultrasonic frequency of 20 kHz, an ultrasonic power of 500 W, and an amplitude of 20%.
[0088] (3) The ultrasonic dispersion was scraped onto a glass plate through a 1000 μm four-sided preparation device and placed in a vacuum oven at 40° C. overnight to obtain a composite proton exchange membrane of 100-110 μm.
[0089] Example 5
[0090] This embodiment provides a composite membrane electrode and a preparation method thereof, as follows:
[0091] (1) The composite proton exchange membrane provided in Example 3 is placed on a vacuum adsorption plate covered with titanium fiber felt, and dried under vacuum adsorption at 60° C. for 20-30 min to preliminarily dry the proton exchange membrane; a mask of suitable size is placed on the surface of the proton exchange membrane, and after being transferred to the vacuum adsorption plate, a plastic scraper is used to gently scrape the proton exchange membrane and the mask around to ensure that there are no bubbles around the mask and the proton exchange membrane and that they fit tightly; the heating temperature of the vacuum adsorption plate is then adjusted to 90° C., and drying is continued for 10 min to flatten the proton exchange membrane;
[0092] (2) After the IrO2 / Pt catalyst, n-propanol, SPSF and ultrapure water are fully mixed, the catalyst slurry is obtained by ultrasonic dispersion using a cell disruptor;
[0093] (3) Spray the cathode catalyst layer with the cathode catalyst slurry, and continue to dry for 30 minutes after spraying to ensure that the solvent is completely volatilized; turn over, fix the proton exchange membrane in the same way, and spray the anode catalyst layer. After spraying, continue to dry for 30 minutes to allow the solvent to completely volatilize; carefully remove the mask, mark the anode and cathode, and place the membrane electrode with a flat surface morphology in a sample bag for use. The anode catalyst loading is about 2.0 mg Ir / cm 2 , the cathode catalyst loading is about 0.2 mg Pt / cm 2 .
[0094] Example 6 (Example 6-1 to Example 6-4)
[0095] This embodiment provides a composite membrane electrode and a method for preparing the same.
[0096] The difference from Example 5 is that in this example, the composite proton exchange membrane used is provided by Example 4, and the specific preparation method is as follows:
[0097] (1) The composite proton exchange membrane provided in Example 4 is placed on a vacuum adsorption plate covered with titanium fiber felt, and dried under vacuum adsorption at 60° C. for 20-30 min to preliminarily dry the proton exchange membrane; a mask of suitable size is placed on the surface of the proton exchange membrane, and after being transferred to the vacuum adsorption plate, a plastic scraper is used to gently scrape the proton exchange membrane and the mask around to ensure that there are no bubbles around the mask and the proton exchange membrane and that they fit tightly; the heating temperature of the vacuum adsorption plate is then adjusted to 90° C., and drying is continued for 10 min to flatten the proton exchange membrane;
[0098] (2) After the IrO2 / Pt catalyst, solvent, SPSF and ultrapure water are fully mixed, the catalyst slurry is obtained by ultrasonic dispersion using a cell disruptor;
[0099] (3) Spray the cathode catalyst layer with the cathode catalyst slurry, and continue to dry for 30 minutes after spraying to ensure that the solvent is completely volatilized; turn over, fix the proton exchange membrane in the same way, and spray the anode catalyst layer. After spraying, continue to dry for 30 minutes to allow the solvent to completely volatilize; carefully remove the mask, mark the anode and cathode, and place the membrane electrode with a flat surface morphology in a sample bag for use. The anode catalyst loading is about 2.0 mg Ir / cm 2 , the cathode catalyst loading is about 0.2 mg Pt / cm 2 .
[0100] Comparative Example 1
[0101] This comparative example provides a composite membrane electrode and a preparation method thereof.
[0102] The difference from Example 5 is that in this comparative example, the silicon dioxide used in the composite proton exchange membrane is the raw material provided in the preparation example (silicon dioxide particles obtained by hydrolysis).
[0103] Comparative Example 2
[0104] This comparative example provides a membrane electrode and a method for preparing the same.
[0105] The difference from Example 5 is that in this comparative example, no hydrogen-conducting hybrid silica particles are added to the proton exchange membrane used, which is denoted as SPSF.
[0106] Performance Test 2
[0107] The samples provided in the embodiment were tested for performance in the following manner:
[0108] (1) Microscopic morphology: The microscopic morphology of Example 2-1 was observed using a transmission electron microscope. Figure 1 ,Depend on Figure 1 It can be seen that the average particle size of the obtained hydrogen-conducting hybrid silica particles is about 150-200 nm;
[0109] (2) Energy spectrum analysis: Figure 2 The energy spectrum result diagram of the sample provided in Example 2-1 is Figure 2 It was found that the imidazole polymer was grafted onto the surface of the hydrogen conductive hybrid silica particles.
[0110] (3) Grafting amount test: The grafting amount was tested using a thermogravimetric analyzer. The test results show that the grafting amount of the sample provided in Example 2-1 is 5.5%. At the same time, the test results show that in the grafting polymerization reaction using the ultrasound-aeration irradiation cycle, the grafting amount after 12 irradiation cycles is the highest, and the grafting amount decreases after more than 12 cycles.
[0111] (4) The interfaces of the samples provided in Examples 5-6 and Comparative Example 1 were observed by scanning electron microscopy. At the same time, the samples were used for hydrolysis to produce hydrogen. After hydrogen production, their cross sections were observed. The results are shown in FIG. Figure 3 ,Depend on Figure 3 It can be seen that:
[0112] The SPSF / SiO2 in Comparative Example 1 has the largest film thickness in the prepared composite PEM due to easy agglomeration of particles and extremely poor dispersibility. However, as can be seen from Examples 5-6, the SPSF / SiO2@PVI membranes prepared by doping SiO2@PVI with different PVI grafting rates have similar film thicknesses due to good interface compatibility.
[0113] In addition, it can be seen that the particle aggregation in the SPSF / SiO2 composite PEM provided in Example 1 is the most serious, and agglomerates are formed by hundreds or thousands of SiO2 nanoparticles. The agglomeration phenomenon of SPSF / SiO2@PVI provided in Examples 5-6 is reduced by comparison. This is because SiO2@PVI has undergone sufficient surface organic modification, and a large number of organic polar groups are carried on the surface, and the interaction with the matrix is greatly enhanced, so the dispersibility is significantly improved. It can be clearly observed that the agglomeration phenomenon of SPSF / SiO2@PVI-3C is the most significant, followed by SPSF / SiO2@PVI-6C. Next is SPSF / SiO2@PVI-9C and SPSF / SiO2@PVI-24C, which have similar dispersibility, and there is basically no large cluster of particles. SPSF / SiO2@PVI-12C has the best dispersion performance, that is, a large number of monodispersed SiO2 hybrid nanoparticles appear.
[0114] At the same time, the dispersion change of SiO2 hybrid nanoparticles in the SPSF matrix follows the same rule as the difference in their PVI grafting density, that is, the composite PEM prepared by SiO2@PVI with a larger PVI grafting density has better particle dispersion and interface compatibility.
[0115] (5) Hydrogen production was carried out by hydrolysis according to the method for producing hydrogen by hydrolysis provided in (4), and the electrolytic water performance of different composite membrane electrodes was recorded. The results are shown in Figure 4 .
[0116] Depend on Figure 4 It can be seen that as the PVI grafting density in the SPSF / SiO2@PVI composite membrane increases (the number of ultrasonic-aeration cycles increases), the electrolytic water performance of the prepared MEA also improves accordingly. This is because the higher the PVI content, the more additional proton transmission channels there are in the composite membrane, and the more likely it is to form a continuous long-range proton transmission channel. In addition, as the PVI content increases, the water absorption rate of the composite PEM increases, which is also an important reason for the improvement of the electrolytic water performance of its MEA.
[0117] SPSF / SiO2@PVI-12C with the highest PVI grafting rate can achieve a current density of 5.41A / cm at 2V. 2 , which is significantly improved compared with pure SPSF. Although the PVI content has a positive effect on the electrolytic water performance of the composite PEM, the electrolytic water performance of SPSF / SiO2@PVI-3C and SPSF / SiO2@PVI-6C is still slightly inferior to that of SPSF, with the current density reaching 2.18A / cm at 2V. 2 and 3.00A / cm 2 , lower than 4.27A / cm of SPSF 2 This may be because although the addition of PVI is beneficial to the construction of additional proton transport channels, when its grafting density does not reach a certain amount, the agglomeration phenomenon in the composite membrane still exists, causing the proton transport of the membrane to be blocked.
[0118] exist Figure 3 and Figure 4 In the embodiment, 3 irradiation cycles are recorded as 3C, the membrane electrode provided in Example 5 is recorded as SPSF / SiO2@PVI-3C, and so on, the sample with 24 irradiation cycles is recorded as SPSF / SiO2@PVI-24C.
[0119] It should be noted that, in this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.
[0120] The above description is only a specific embodiment of the present disclosure, so that those skilled in the art can understand or implement the present disclosure. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present disclosure. Therefore, the present disclosure will not be limited to the embodiments described herein, but will conform to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A hydrogen-conducting hybrid silica particle, characterized in that: The invention comprises modified silicon dioxide particles and imidazole polymers grafted on the surface of the modified silicon dioxide particles, wherein the grafting amount of the imidazole polymers grafted on the surface of the modified silicon dioxide particles is 5.5-13%.
2. The hydrogen-conducting hybrid silica particles according to claim 1, characterized in that The mass ratio of the modified silica particles to the imidazole polymer is (85-95):(5-15); Preferably, the density of hydrogen conducting groups on the surface of the modified silica particles is 0.05-0.2 μmol / m 2 ; Preferably, the modified silica particles are silane coupling agent modified silica particles; Preferably, the silane coupling agent is a silane coupling agent containing a carbon-carbon double bond, and preferably the silane coupling agent is γ-methacryloxypropyltrimethoxysilane; Preferably, the particle size of the silicon dioxide particles is 100-200 nm; Preferably, the silicon dioxide particles are silicon dioxide particles prepared by hydrolysis.
3. The hydrogen-conducting hybrid silica particles according to claim 1 or 2, characterized in that The polymerization monomer of the imidazole polymer is an imidazole compound with a carbon-carbon double bond, preferably vinyl imidazole and / or 1-propylene imidazole.
4. A method for preparing hydrogen-conducting hybrid silica particles according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: (1) reacting silica particles with a silane coupling agent to obtain modified silica particles; (2) Grafting imidazole monomers onto the surface of the modified silica particles and performing an in-situ polymerization reaction to obtain the hydrogen conductive hybrid silica particles.
5. The preparation method according to claim 4, characterized in that: The mass ratio of the silica particles to the silane coupling agent is (1-5):(1-5), preferably 1:1; And / or, the reaction in step (1) is carried out in an alcohol aqueous solution; And / or, the reaction temperature in step (1) is 70-75°C and the reaction time is 4-6h.
6. The preparation method according to claim 4 or 5, characterized in that: Step (2) is: after mixing the modified silica particles and the imidazole monomer in a solvent, a graft polymerization reaction is carried out by an ultrasonic-aeration method to obtain the hydrogen conductive hybrid silica particles.
7. The preparation method according to claim 6, characterized in that: The mass ratio of the modified silica particles to the imidazole monomer is 1:(5-20), preferably 1:10; And / or, in the ultrasound-exposure method, the ultrasound mode is insertion ultrasound with a power of 500-750 W, a frequency of 20-25 kHz, an amplitude of 20-40%, and a temperature of 4-15° C.; And / or, in the ultrasound-exposure method, the number of ultrasound-exposure cycles is 3-24 times.
8. A composite proton exchange membrane, characterized in that: A method of manufacturing a hydrogen-conducting hybrid silica particle comprising a matrix and the hydrogen-conducting hybrid silica particle according to any one of claims 1 to 3 doped in the matrix; Preferably, the mass ratio of the matrix to the hydrogen-conducting hybrid silica particles is 100:(4.5-10); Preferably, the matrix is a sulfonated polymer matrix, more preferably sulfonated polysulfone and / or sulfonated polyetheretherketone.
9. A composite membrane electrode, characterized in that: Comprising the composite proton exchange membrane according to claim 8.
10. A method for preparing the composite membrane electrode according to claim 9, characterized in that: The preparation method comprises: coating cathode catalyst slurry and anode catalyst slurry on both sides of the composite proton exchange membrane respectively and drying them to obtain the composite membrane electrode.